2012
DOI: 10.1194/jlr.m019356
|View full text |Cite
|
Sign up to set email alerts
|

Fifty-three year follow-up of coronary heart disease versus HDL2 and other lipoproteins in Gofman's Livermore Cohort

Abstract: This article is available online at http://www.jlr.org concentrations that were 32% lower for HDL2 and 8% lower for HDL3 (the less buoyant particles) compared with those who did not develop CHD ( 3 ).Gofman's initial observation gave rise to studies by others on the potential clinical utility of HDL2 and HDL3 measurements. Rather than employing Gofman's original methodology, they measured HDL2-and HDL3-cholesterol by precipitation and HDL size classes by nuclear magnetic resonance (NMR) or, more rarely, ultrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
0
10
1
2
Order By: Relevance
“…LDL mass concentrations only weakly affected survival until 85, in contrast to the strong association reported previously between LDL and total and premature CHD . In the current study, the significant inverse relationship between LDL mass and the odds of surviving until 85 became nonsignificant when adjusted for other risk factors, notably cigarettes/day smoked (adjusted P = .15), systolic blood pressure (adjusted P = .06), and total cholesterol (adjusted P = .14), the last having strong colinearity with LDL mass concentrations (correlated r = 0.75 at baseline).…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…LDL mass concentrations only weakly affected survival until 85, in contrast to the strong association reported previously between LDL and total and premature CHD . In the current study, the significant inverse relationship between LDL mass and the odds of surviving until 85 became nonsignificant when adjusted for other risk factors, notably cigarettes/day smoked (adjusted P = .15), systolic blood pressure (adjusted P = .06), and total cholesterol (adjusted P = .14), the last having strong colinearity with LDL mass concentrations (correlated r = 0.75 at baseline).…”
Section: Discussioncontrasting
confidence: 95%
“…HDLs may be separated into two major subfractions: larger, more‐buoyant HDL2 particles (1.063–1.125 g/mL) and smaller, less‐buoyant HDL3 particles (1.125–1.210 g/mL) . Recently, using a direct measurement of total mass, it was reported that the lowest quartiles of HDL2 and HDL3 were associated prospectively with greater risk of CHD …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2, 10, 25 Prior studies that evaluated HDL size using these other subfractionation methods have mostly found inverse association for large HDL size with CHD but equivocal results for smaller HDL size. 2634 …”
Section: Discussionmentioning
confidence: 99%
“…Alagona et al [17] Asymptomatic subjects 89 Associated inversely with IMT No association with IMT Sharrett et al [18] Healthy subjects 12.339 Lower for cases Lower for cases Mora et al [19] Female subjects 27.673 Relative to lowest quintile No significance for medium and small size HDLs Williams et al [20] Healthy subjects 1905 Lowest quartile of HDL2-mass predicted greater incident CHD Lowest quartile of HDL3-mass predicted incident CHD Williams et al [21] CHD/controls 1905 Lowest HDL2-mass quartile increased the risk for total CHD and premature CHD Lowest HDL3-mass quartile increased the risk for total CHD and premature CHD Lamon-Fava et al [22] CHD 256 Coronary atherosclerosis progression unrelated Coronary atherosclerosis progression unrelated to changes. Greater progression for greater reductions.…”
Section: Studymentioning
confidence: 97%